The Indo-Ceylon problem : the politics of immigrant labour - Jayasinghe, W. T. (Pannipitiya : Stamford Lake Publication, 2002)
Historical account of South Indian immigrant labor in tea and coffee plantations in Sri Lanka.
Keywords: Foreign workers, East Indian -- Sri Lanka -- History; Tea plantation workers -- Sri Lanka -- History; Coffee plantation workers -- Sri Lanka -- History; Sri Lanka -- Emigration and immigration -- History